Mycosynthesis of anticancer drug taxol by Aspergillus oryzae, an endophyte of Tarenna asiatica, characterization, and its activity against a human lung cancer cell line. (March 2020) - Suresh, Gopal; Kokila, Dhanasegaran; Suresh, Thirunavukarasu Chitrikha; Kumaran, Subramanian; Velmurugan, Palanivel; Vedhanayakisri, Kaliyappan Amballandi; Sivakumar, Subpiramaniyam; Ravi, Arumugam Veera
Abstract: Taxol is a member of the taxane family of chemotherapy drugs, which includes cabazitaxel and docetaxel that have a promising role as anti-cancer drugs for specific human cancers. Hence, in order to meet the requirement, an alternative source for Taxol production, such as filamentous fungi is needed. In this study, a different endophytic fungus was obtained from a particular medicinal plant, Tarenna asiatica, and was selected for Taxol production. Among 28 screened fungi, only six fungal species produced Taxol in the modified liquid medium. The novel Taxol-producing endophytic fungi were identified through morphological and molecular identification using DNA sequencing and phylogenetic tree construction as Aspergillus oryzae . The structure of Taxol obtained from A. oryzae was identified with the appropriate control using an ultraviolet–visible (UV–Vis) spectrophotometer (235 nm), thin layer chromatography (TLC), liquid chromatography-mass spectrometry (LC-MS), and Fourier-transform infrared (FTIR) analysis. The fungal Taxol (95.04 μg/L) from the A. oryzae exhibits potent in vitro activity against selected cell line (Human Lung Cancer Cell Line- NCI–H460).